Śivagomantaka : dona aṅkī nāṭaka - Vāgha, Vishṇū Suryā. (Mhādrola, Govā : Indū Sūrya Prakāśana, 2008)
On Shivaji, Raja, 1627-1680, Maratha ruler.
Play.
In Marathi.
Keywords: Shivaji, -- Raja, -- 1627-1680 -- Drama; Shivaji, -- Raja, -- 1627-1680.; Drama